Cell-Penetrating Dabcyl-Containing Tetraarginines with Backbone Aromatics as Uptake Enhancers - Mo'ath Yousef; Ildikó Szabó; József Murányi; Françoise Illien; Dóra Soltész; Csaba Bató; Gabriella Tóth; Gyula Batta; Péter Nagy; Sandrine Sagan; Zoltán Bánóczi (MDPI AG, 2022)
Cell-penetrating peptides represent an emerging class of carriers capable of effective cellular delivery. This work demonstrates the preparation and investigation of efficient CPPs. We have already shown that the presence of 4-((4-(dimethylamino)phenyl)azo)benzoic acid (Dabcyl) and Trp greatly increase the uptake of oligoarginines. This work is a further step in that direction. We have explored the possibility of employing unnatural, aromatic amino acids, to mimic Trp properties and effects. The added residues allow the introduction of aromaticity, not as a side-chain group, but rather as a part of the sequence. The constructs presented exceptional internalization on various cell lines, with an evident structure-activity relationship. The CPPs were investigated for their entry mechanisms, and our peptides exploit favorable pathways, yet one of the peptides relies highly on direct penetration. Confocal microscopy studies have shown selectivity towards the cell lines, by showing diffuse uptake in FADU cells, while vesicular uptake takes place in SCC-25 cell line. These highly active CPPs have proved their applicability in cargo delivery by successfully delivering antitumor drugs into MCF-7 and MDA-MB-231 cells. The modifications in the sequences allow the preparation of short yet highly effective constructs able to rival the penetration of well-known CPPs such as octaarginine (Arg8).